The Impact of Economic Factors Habits Patriarchal System and Psychological Disorders on Violence Against Children and Women in North Sumatra - Lubis, Syaddan Dintara (Universitas Islam Negeri Sumatera Utara, 2023)
The results of interviews at the Children's and Women's Empowerment Service which were carried out were aimed at proving that violence that occurs against children and women can be motivated by poor finances, our daily habits, our country's social system which is still patriarchal, and the existence of psychological and mental disorders towards perpetrators of violence against children and women. This research is based on quantitative data based on our interviews at D3AKB which will strengthen the data that will be included in this research.